Late diagnosis of Bardet-Biedl syndrome in an 18-year-old patient − a case report and literature review - Sobieszczańska-Droździel, Aleksandra; Kalicka-Żuk, Karolina; Bieniaś, Beata (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Bardet-Biedl syndrome (BBS) is a rare, autosomal recessive multi-system ciliopathy. Its diagnosis is based on a constellation of characteristic clinical symptoms that appear in childhood, including kidney defects, obesity, retinal dystrophy, polydactyly, intellectual dysfunction, and hypogonadism. We present a case of an 18-year-old girl with a postnatal diagnosis of postaxial polydactyly of the feet and hands and bilateral cutaneous syndactyly of the 2nd and 3rd toes, who successively developed most of the typical BBS manifestations. Despite this, the correct diagnosis was made only 3 months before adulthood in our clinic, to which the patient was referred because of suspicion of hypertension. Molecular testing confirmed the clinical diagnosis of BBS (homozygous variant c.619-1G>C in the BBS5 gene). The presented case is an example of a delayed diagnosis of BBS. The main reason was the lack of a comprehensive assessment of the multi-system disorders characteristic of BBS.